Segmentation of anthropometric data of the Brazilian’ female population - Capelassi, Carla (2018)
The researches concerning the measurements of the human body in Brazil are still very few and the anthropometric data related with the Brazilian women is widely diversified due to some aspects such as the vastness of the country and a huge miscegenation of races. The results obtained through the utilization of a 3D body scanner were segmented into four categories, namely: age, region of origin, race and shape. The aim of this study is to provide more accurate and reliable measurements and information concerning the different types of body shapes for the clothing sizing systems directed to the industry specialized in the mass production of clothing, and, therefore, allow clothing to fit appropriately on the wearer’s body in such a way as to make her more confident and satisfied with the clothing available in the market but also access higher levels of comfort.